Sensitive detection of measles virus infection in the blood and tissues of humanized mouse by one-step quantitative RT-PCR - Ikeno, Shota; Suzuki, Moto-omi; Muhsen, Mahmod; Ishige, Masayuki; Kobayashi, Mie; Ohno, Shinji; Takeda, Makoto; Nakayama, Tetsuo; Morikawa, Yuko; Terahara, Kazutaka; Okada, Seiji; Takeyama, Haruko; et al. (Frontiers in Microbiology, 2013)
Live attenuated measles virus (MV) has long been recognized as a safe and effective vaccine, and it has served as the basis for development of various MV-based vaccines. However, because MV is a human-tropic virus, the evaluation of MV-based vaccines has been hampered by the lack of a small-animal model. The humanized mouse, a recently developed system in which an immunodeficient mouse is transplanted with human fetal tissues or hematopoietic stem cells, may represent a suitable model. Here, we developed a sensitive one-step quantitative reverse transcription (qRT)-PCR that simultaneously measures nucleocapsid (N) and human RNase P mRNA levels. The results can be used to monitor MV infection in a humanized mouse model. Using this method, we elucidated the replication kinetics of MV expressing enhanced green fluorescent protein both in vitro and in humanized mice in parallel with flow-cytometric analysis. Because our qRT-PCR system was sensitive enough to detect MV expression using RNA extracted from a small number of cells, it can be used to monitor MV infection in humanized mice by sequential blood sampling.